2020
DOI: 10.3390/foods10010033
|View full text |Cite
|
Sign up to set email alerts
|

Food–Drug Interactions with Fruit Juices

Abstract: Fruit juices contain a large number of phytochemicals that, in combination with certain drugs, can cause food–drug interactions that can be clinically significant and lead to adverse events. The mechanisms behind such interactions are in most cases related to phytochemical interference with the activity of cytochrome P450 metabolizing enzymes (CYPs) or drug transporters. Moreover, alterations in their activity can have a clinical relevance if systemic exposure to the drug is decreased or increased, meaning tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 81 publications
0
10
0
2
Order By: Relevance
“…Further studies showed that a number of other fruit juices (e.g., apple and orange) are also able to change the pharmacological effects of drugs by altering activity and expression of intestinal OATP1A2, CYP3A4 or Pgp or by direct interaction with the drugs [ 74 ]. However, other reports indicate that it is difficult to estimate the pharmacodynamic outcome of these effects due to a high variability of fruit juice composition and the differences among individuals [ 78 , 79 ]. Furthermore, the daily uptake of grapefruit juice is moderate in most countries and therefore, only a few cases might contribute to the clinical relevance of fruit juice–drug interactions [ 80 ].…”
Section: Dietmentioning
confidence: 99%
“…Further studies showed that a number of other fruit juices (e.g., apple and orange) are also able to change the pharmacological effects of drugs by altering activity and expression of intestinal OATP1A2, CYP3A4 or Pgp or by direct interaction with the drugs [ 74 ]. However, other reports indicate that it is difficult to estimate the pharmacodynamic outcome of these effects due to a high variability of fruit juice composition and the differences among individuals [ 78 , 79 ]. Furthermore, the daily uptake of grapefruit juice is moderate in most countries and therefore, only a few cases might contribute to the clinical relevance of fruit juice–drug interactions [ 80 ].…”
Section: Dietmentioning
confidence: 99%
“…Часть из них обусловлена взаимодействием ЛС как между собой, так и с продуктами питания [2,3]. В инструкциях по применению многих ЛС описаны изменения фармакокинетики, которые могут наблюдаться в случае их одновременного приема с пищей, однако эти данные получают в экспериментальных условиях при потреблении стандартизированной диеты, содержащей большое количество жиров [4][5][6][7][8][9][10][11][12][13][14][15]. При этом реальный рацион питания пациента не соответствует качественному и количественному составу стандартизированной диеты, поэтому фармакокинетический и фармакодинамический профиль ЛС в условиях реальной практики может отличаться от экспериментальных данных.…”
Section: взаимодействие лекарствunclassified
“…Это указывает на то, что вероятность развития лекарственных взаимодействий с соком горького апельсина повышена только для тех ЛС, биодоступность которых в большей степени определяется активностью CYP3A4 в энтероцитах и в меньшей степени P-гликопротеина [29,30]. Так, в клиническом исследовании при совместном применении силденафила, который обладает выраженным пресистемным метаболизмом (биодоступность около 40%), с соком горького апельсина у здоровых добровольцев (силденафил в дозе 50 мг один раз в сутки в течение 3 дней подряд одновременно с 250 мл сока или воды) было выявлено увеличение AUC и C max ингибитора фосфодиэстеразы 5 на 44% [31,32].…”
Section: сок горького апельсинаunclassified
“…Since raw materials used for production of functional foods commonly employ suitable raw materials (fruits, vegetables, legumes etc.) they are mixed well with probiotics and/or biologically active compounds from plant and/or animal origin [ 10 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. General direction for production of such foods is to have adherence to local diets (e.g., Mediterranean diets) while supplying local food markets with healthy alternatives for consumers.…”
mentioning
confidence: 99%
“…For instance, good example represents European SFS-funding program or 3D-SustJuice project funded by the Croatian Science Foundation (Hurdle technology and 3D printing for sustainable fruit juice processing and preservation) which is strongly related to this special issue and serves as a vehicle for dissemination of important data to scientific community [ 23 ]. Consequently, this Special Issue of Foods collected data relevant to sustainable functional food production [ 1 , 10 , 12 , 17 , 22 , 24 , 25 , 26 ], hurdle technology [ 12 ], advanced food processing [ 1 , 2 , 12 , 17 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], functional beverages [ 1 , 12 , 17 , 18 , 25 , 33 ], probiotics and BACs [ 1 , 2 , 12 , 17 , 20 , 21 , 22 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], and authentic fruits [ 7 , 25 , 30 ].…”
mentioning
confidence: 99%